Expression and significance of telomerase in the nucleus pulposus tissues of degenerative lumbar discs - ZHANG, XU (Biomed Rep, 2015)
The pathogenesis of lumbar disc degeneration is extremely complex, and the expression and role of telomerase in degenerative lumbar disc tissues remains unclear. The aim of the present study was to detect telomerase expression in nucleus pulposus tissues of degenerative lumbar discs and to explore the correlation between telomerase expression and other factors typical of disc degeneration. A total of 8 patients with degenerative nucleus pulposus were included as the experimental group and compared with 8 control patients without evident lumbar disc degeneration. The expression of telomerase in nucleus pulposus tissues was detected by immunohistochemical staining. ELISA was performed to determine the differential expression of telomerase, type II collagen and chondroitin sulfate between the two groups. In addition, a correlation analysis was performed to form associations between these factors. Finally, 5 cases in the experimental group and 5 in the control group were involved in the analysis. Immunohistochemistry results showed that telomerase expression in the experimental group was significantly lower compared to the control group and the percentage in the unit field of view showed significant differences between the two groups (P<0.05). Similarly, the ELISA test results showed lower expression levels of telomerase, type II collagen and chondroitin sulfate in the experimental group when compared with the control group (P<0.05). The correlation analysis revealed that telomerase was positively correlated with type II collagen and chondroitin sulfate (correlation coefficients, 0.673 and 0.528, respectively; P<0.01). In conclusion, telomerase is involved in the degeneration process of nucleus pulposus tissue in lumbar discs and has a positive correlation with other factors typically associated with degeneration.